Oak extractive‐induced stress reveals the involvement of new enzymes in the early detoxification response of Phanerochaete chrysosporium. (5th October 2018) - Fernández‐González, Antonio José; Valette, Nicolas; Kohler, Annegret; Dumarçay, Stéphane; Sormani, Rodnay; Gelhaye, Eric; Morel‐Rouhier, Mélanie
Summary: Extensive evidence showed that the efficiency of fungal wood degradation is closely dependent on their ability to cope with the myriad of putative toxic compounds called extractives released during this process. By analysing global gene expression of Phanerochaete chrysosporium after short oak extractive treatment (1, 3 and 6 h), we show that the early molecular response of the fungus concerns first mitochondrial stress rescue followed by the oxidation and finally conjugation of the compounds. During these early responses, the lignolytic degradative system is not induced, rather some small secreted proteins could play an important role in cell protection or signaling. By focusing on the functional characterization of an hitherto uncharacterized glutathione transferase, we show that this enzyme interacts with wood molecules suggesting that it could be involved in the detoxification of some of them, or act as a scavenger to prevent their cytosolic toxicity and favour their transport.